2023
DOI: 10.1186/s40068-023-00302-x
|View full text |Cite
|
Sign up to set email alerts
|

Environmental pollution loads on surface water chemistry and potentially ecological risks of inland aquatic ecosystem in South-Eastern State, Nigeria

Abstract: The study assessed water chemistry of Nworie inland aquatic ecosystem in South eastern, Nigeria from January, 2020 to December 2022. Water samples were taken from the upper, middle, and lower river at 200 m interval. Data collected were subjected to multivariate analyses. Results of physicochemical tracers indicated mean CaCO3, Ca2+&Chemical Oxygen Demand (COD) to be 172.8 mg/l, 103.1 mg/l, 16.50 mg/l respectively above the World Health Organisation (WHO) critical limits, while turbidity (NTU), dissolved o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 130 publications
3
3
0
Order By: Relevance
“…Cultivated floodplains have more silt composition than upland and midstream areas. This is in agreement with Ubuoh (2016), during the studies on the effect of flooding on soil quality in Abakaliki-Nigeria, which concluded that such results are a clear sign of more soil fertility that favours crop production. Soils in floodplains have a higher composition of clay than sand and silt, making floodplains more fertile and favourable for crop production (Ogbodo, 2011) )…”
Section: Physical Properties Results and Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Cultivated floodplains have more silt composition than upland and midstream areas. This is in agreement with Ubuoh (2016), during the studies on the effect of flooding on soil quality in Abakaliki-Nigeria, which concluded that such results are a clear sign of more soil fertility that favours crop production. Soils in floodplains have a higher composition of clay than sand and silt, making floodplains more fertile and favourable for crop production (Ogbodo, 2011) )…”
Section: Physical Properties Results and Discussionsupporting
confidence: 92%
“…According to Montgomery (2017), this result implies that there is a significant difference between the upland and the floodplains fallowed for over a year for Nitrogen. This result supports findings by Ubuoh (2016), during the study of the effects of flooding on soil quality in Abakaliki agro-ecological zone, Nigeria that concluded that there were significant differences among treatments in total Nitrogen, a strong indication of rapid fruiting and ripening of fruits. Flooding lowlands fallowed for a year posted the highest percentage at 0.32%, followed by the floodplains fallowed for over a year at 0.20% as compared to the lowest posting of 0.09% from the upland.…”
Section: Chemical Properties Results and Discussionsupporting
confidence: 91%
See 3 more Smart Citations